1990
DOI: 10.2307/3282626
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni Modulation of Phagocytosis in Biomphalaria glabrata

Abstract: Both short-term (3 hr) exposure of Biomphalaria glabrata snails (M-line and 13-16-R1) to Schistosoma mansoni (PR1) miracidia and in vitro incubation of parasite sporocysts with host hemolymph components altered host phagocytic ability. Hemocytes obtained from susceptible (M-line) snails that had been exposed to parasite miracidia for 3 hr showed reduced levels of phagocytosis of yeast cells in vitro compared to hemocytes from unexposed individuals. Incubation of whole hemolymph with sporocysts in vitro also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 15 publications
0
19
0
3
Order By: Relevance
“…La disminución en el número de hemocitos circulantes que se observan en los ostiones con RM, responde al patrón determinado para otros moluscos parasitados (Fryer & Bayne, 1990;Noda & Sato, 1990;Ford et al, 1993), lo que se explicaría por su infiltración a los tejidos y/o a su agregación en la hemolinfa.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…La disminución en el número de hemocitos circulantes que se observan en los ostiones con RM, responde al patrón determinado para otros moluscos parasitados (Fryer & Bayne, 1990;Noda & Sato, 1990;Ford et al, 1993), lo que se explicaría por su infiltración a los tejidos y/o a su agregación en la hemolinfa.…”
Section: Discussionunclassified
“…Estas células circulantes están presentes en la hemolinfa, pero también son capaces de salir de la circulación y migrar a otros tejidos del animal donde pueden agregarse para restringir la infección o alguna lesión tisular (Bachère et al, 2004). Su ca-pacidad de fagocitosis es una de las funciones esenciales de los hemocitos para eliminar agentes exó-genos como bacterias o protozoos (Bayne, 1990), en este caso se induce la producción de especies reactivas de oxígeno (Nappi & Ottaviani, 2000;Lambert et al, 2003). En bivalvos pectínidos la capacidad fagocítica se ha evaluado en Pecten maximus con diversos tipos de bacterias y levaduras (Lambert & Nicolas, 1998).…”
unclassified
See 1 more Smart Citation
“…In addition, it has been demonstrated that sporocysts release glycoproteins (excreted/secreted products) that bind to carbohydrate-binding receptors on the haemocyte cell surface to attenuate the initial cellular recognition of the parasite (Johnston & Yoshino 2001). These molecules can inhibit IDS mechanisms (Adema & Loker 1997) by suppressing the synthesis of many haemocyte molecules (Lodes et al 1991) or by reducing haemocyte motility and phagocytic activity (Fryer & Bayne 1990, Lodes & Yoshino 1990). Other important parasite escape mechanisms include the use of molecular mimicry, likely through the production of sporocyst surface membrane molecules similar to those present on the host, and the ability of the parasite to absorb host antigens (Yoshino & Bayne 1983, Damian 1987, Salzet et al 2000, Lehr et al 2008, Peterson et al 2009, van Die & Cummings 2010.…”
mentioning
confidence: 99%
“…Parasite escape mechanisms that respond to the host IDS can assure the survival and adaptability of the parasite (Yoshino & Bayne 1983, Adema & Loker 1997. Previous studies have demonstrated that success of the infection depends on the parasite interfering with the mollusc IDS (Fryer & Bayne 1990). The parasite can disturb the IDS by producing proteases (Yoshino et al 1993) and by the action of enzymes that neutralise reactive oxygen species (Connors & Yoshino 1990).…”
mentioning
confidence: 99%